Carbon dioxide injection for enhanced gas recovery and storage (reservoir simulation) - Chawarwan Khan; Robert Amin; Gary Madden (Egyptian Journal of Petroleum)
CO2 injection for enhanced oil recovery (EOR) had been broadly investigated both physically and economically. The concept for enhanced gas recovery (EGR) is a new area under discussion that had not been studied as comprehensively as EOR. In this paper, the “Tempest” simulation software was used to create a three-dimensional reservoir model. The simulation studies were investigated under different case scenarios by using experimental data produced by Clean Gas Technology Australia (CGTA). The main purpose of this study is to illustrate the potential of enhanced natural gas recovery and CO2 storage by re-injecting CO2 production from the natural gas reservoir. The simulation results outlined what factors are favourable for the CO2-EGR and storage as a function of CO2 breakthrough in terms of optimal timing of CO2 injection and different injection rates. After analysing the results for each case scenario, it had been concluded that CO2 injection can be applied to increase natural gas recovery simultaneously sequestering a large amount of the injected CO2 for this particular gas reservoir. In addition, various CO2 costs involved in the CO2-EGR and storage were investigated to determine whether this technique is feasible in terms of the CO2 content in the production as a preparation stage to achieve the economic analysis for the model.